2017
DOI: 10.1038/s41598-017-01257-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 on the fitness and potential population damage of Helicoverpa armigera based on two-sex life table

Abstract: We evaluated the direct effects of three different atmospheric CO2 concentrations (380 ppm, 550 ppm and 750 ppm) on the population parameters of the cotton bollworm, Helicoverpa armigera fed an artificial diet. The life history and fitness of H. armigera were analyzed using an age-stage, two-sex life table. Our results showed significantly longer larval durations and lower female pupal weight under elevated CO2 than under ambient CO2. Additionally, the fecundity of H. armigera was lower under elevated CO2 than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Akbar et al (2016) reported that increased CO 2 negatively affected larval survival, larval development, pupation and adult emergence of H. armigera , while pupal period, pupal weight and individual fecundity increased. Liu et al (2017) also showed that H. armigera would exhibit lower fitness in the future with increasing CO 2 concentration because the population size was lower under elevated CO 2 than under ambient CO 2 . Xie et al (2015) reported that Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) fed on an artificial diet reduced larval food digestibility and utilization efficiency as well as decreased fitness‐related parameters including higher mortality, lower pupal weight, and longer development times under elevated CO 2 treatments (550 ppm and 750 ppm).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Akbar et al (2016) reported that increased CO 2 negatively affected larval survival, larval development, pupation and adult emergence of H. armigera , while pupal period, pupal weight and individual fecundity increased. Liu et al (2017) also showed that H. armigera would exhibit lower fitness in the future with increasing CO 2 concentration because the population size was lower under elevated CO 2 than under ambient CO 2 . Xie et al (2015) reported that Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) fed on an artificial diet reduced larval food digestibility and utilization efficiency as well as decreased fitness‐related parameters including higher mortality, lower pupal weight, and longer development times under elevated CO 2 treatments (550 ppm and 750 ppm).…”
Section: Discussionmentioning
confidence: 99%
“…The most important thing is to discover the effect of elevated CO 2 on insect distribution and occurrence in order to predict the change of insect population dynamics and community structure in potential future environments. The longer developmental duration and higher mortality of H. armigera larvae under elevated CO 2 resulted in lower population sizes than those under ambient CO 2 (Liu et al 2017; Wu et al 2006; Yin et al 2010). Choi et al (2018) proposed a possible mechanism about how slightly increase of CO 2 level can directly affect insect life using the pheromone communication of H. armigera .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis examining the effects of elevated CO 2 on the life history traits of insects found that while the abundance of foliage feeders tends to decrease, phloem feeders on average tend to perform better under elevated CO 2 ( Robinson et al, 2012 ). Generally, elevated CO 2 shows negative effects on chewing insects with a decline in the foliar nitrogen content of host plants; as a recent study on the cotton bollworm, Helicoverpa armigera , showed that larval durations were significantly prolonged by elevated CO 2 , additionally, female pupal weight, fecundity, and total population size under elevated CO 2 were lower than ambient CO 2 ( Liu et al, 2017 ). In contrast, aphids, as a kind of phloem feeders, are considered the only feeding guild that positively responds to elevated CO 2 .…”
Section: Discussionmentioning
confidence: 99%